Evaluasi Implementasi Kebijakan Perubahan Status IAIN Ar-Raniry Menjadi UIN - Ibrahim, Lukman (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2012)
The idea to change the status of the Ar-Raniry State Institute of Islamic Studies (IAIN Ar-Raniry) to be the Islamic State University of Ar-Raniry was based on the aspirations of the majority of education stakeholders in Aceh. This change entails a wide range of mandates to conduct teaching-learning processes for various fields of studies. This, therefore, will require that campus infrastructures, teaching-learning facilities, and funding sources be ready. This article is based on the research results revealing the supports for the status change were strong. However, the quantity and quality of the stakeholders’ involvements, either at IAIN Ar-Raniry, regional, or national levels, are considerably low. In addition, the quantity and quality of teaching and administrative staffs at every unit of education within IAIN and the number of campus infrastructures and teaching-learning facilities are far from enough. Thus, the leaders of IAIN Ar-Raniry should continuously benefit from the supports given to IAIN Ar-Raniry with intensive information dissemination, communication, and lobbying. Such intensive efforts should also be accompanied by developing each department and faculty, human resources, and campus facilities and infrastructures. This can be done through a roadmap rational and strong formulation that involves all elements within IAIN Ar-Raniry.